2020
DOI: 10.3389/fvets.2020.00085
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Blood Groups DEA 1, DEA 4, DEA 5, Dal, and Kai 1/Kai 2 in Different Canine Breeds From a Diagnostic Laboratory in Germany

Abstract: More than twelve blood group systems have been described in dogs, but little is known about their distribution frequencies within breed populations. Here, we report on an extensive typing survey carried out using available reagents and either established or new clinical kits in purebred dogs from Germany. Leftover anticoagulated blood samples were examined using an immunochromatographic strip method for DEA 1, a gel column technique for Dal and Kai 1/2, and new card agglutination tests for DEA 4 and DEA 5 (whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 43 publications
(103 reference statements)
2
34
0
Order By: Relevance
“…Information on the prevalence of different blood types in various breeds aids the selection of blood donors for inclusion in a blood donor program [2]. This study showed a similar prevalence of DEA 1, 7 and 4 to that reported in previous studies in the same, and in different, geographic areas [16,17,19,22].…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Information on the prevalence of different blood types in various breeds aids the selection of blood donors for inclusion in a blood donor program [2]. This study showed a similar prevalence of DEA 1, 7 and 4 to that reported in previous studies in the same, and in different, geographic areas [16,17,19,22].…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore a study [21] in Korea showed that dogs had no naturally occurring anti-Kai 1 and Kai 2 alloantibodies. A further survey in Germany found similar proportions of positive and negative of DEA 1,4, Kai 1 and 2 and Dal blood types to those in North America [22].…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In 2007, the Dal blood group was identified in an anemic Dalmatian dog through the use of a gel agglutination assay [ 13 ]. The Dal blood group is characterized by anti- Dal alloantibodies; Dal is an antigen in red cells associated with anti-Dal alloantibody production [ 10 , 13 , 14 , 15 , 16 ]. Another blood group involves the Kai systems produced by mouse hybridoma techniques [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%